SEMELHANÇAS E DISCORDÂNCIAS ENTRE MÉTODOS DE ADAPTABILIDADE E ESTABILIDADE - BARROSO, Laís Mayara Azevedo; NASCIMENTO, Moysés; NASCIMENTO, Ana Carolina Campana; SILVA, Fabyano Fonseca e; FERREIRA, Reinaldo de Paula; CRUZ, Cosme Damião; TEIXEIRA, Filipe Ribeiro Formiga; TEODORO, Paulo Eduardo (Brazilian Journal of Biometrics, 2017)
The objective of this work was to evaluate the influence of discrepant points on the classification of genotypes obtained through methods of adaptability and stability that are different from the statistical concepts used in its construction (Eberhart and Russell, nonparametric regression, expanded centroid and Lin and Binns). For this, it was used data from an experiment on dry matter yield of 92 genotypes of alfalfa (Medicago sativa L.) evaluated in 20 environments. The results indicated that the presence of discrepant points changed the classification of genotypes in all tested methodologies. Among all methodologies evaluated, the extended centroid method showed less sensitivity to the presence of outliers.